Características luminescentes do sistema relaxor PLMN-13PT dopado com érbio em transições de fase polar - Correr, Guilherme Ilário (2021)
Structural and polar phase transitions are important for materials studies, specially for normal and relaxor ferroelectrics. These states influence the materials physical characteristics, which are observable by many characterization techniques. In this context, the main objective of this monograph was the study of luminescent characteristics of the relaxor ferroelectric ceramic system PLMN-13PT doped with trivalent Erbium ions, when influenced by temperature and electric field changes, highlighting polar state transitions. Our results show the parameters as the amplitude and peak position of Erbium emissions (excited by Er-resonant 442 nm wavelength) by six conditions of electric field and temperature. From dipole glass model theory for relaxor ferroeletrics, and assuming the existence of polar nanorregions (PNR), changes in emission are related to electric field dependence and some anomalies are observed, mainly next to the freezing relaxor transition temperature.